2015
DOI: 10.1093/czoolo/61.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and introgression: Discovery and mapping of thousands of species-diagnostic SNPs using RAD sequencing

Abstract: Invasive hybridization and introgression pose a serious threat to the persistence of many native species. Understanding the effects of hybridization on native populations (e.g., fitness consequences) requires numerous species-diagnostic loci distributed genome-wide. Here we used RAD sequencing to discover thousands of single-nucleotide polymorphisms (SNPs) that are diagnostic between rainbow trout (RBT, Oncorhynchus mykiss), the world’s most widely introduced fish, and native westslope cutthroat trout (WCT, O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…A reference genome sequence, a poorly assembled set of genomic scaffolds, or even a set of previously identified RAD loci can greatly improve the ability to filter paralogous or repetitive sequences, identify insertion-deletion variation, and remove non-target DNA sequence (e.g. bacterial contamination) 54 . A well-assembled reference genome provides further advantages.…”
Section: How To Design a Radseq Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A reference genome sequence, a poorly assembled set of genomic scaffolds, or even a set of previously identified RAD loci can greatly improve the ability to filter paralogous or repetitive sequences, identify insertion-deletion variation, and remove non-target DNA sequence (e.g. bacterial contamination) 54 . A well-assembled reference genome provides further advantages.…”
Section: How To Design a Radseq Studymentioning
confidence: 99%
“…For instance, the development of de novo reference genomes for non-model species is becoming increasingly feasible as sequencing and assembly technologies continue to improve 62,63 , and such a reference provides numerous advantages for analysis of RADseq data from population-level sampling 25,49,50,54 . Transcriptome sequencing can also complement RADSeq data by targeting coding (and presumably functional) sequence, whereas RADseq interrogates both coding and non-coding loci.…”
Section: How To Design a Radseq Studymentioning
confidence: 99%
“…Despite this, having even a draft genome (in 1000s of scaffolds) can help improve data analyses in many ways including the following: (a) reliable discovery of SNPs (e.g., avoiding duplicated loci), (b) reducing genotyping error rates (Hand et al., 2015; Shafer et al., 2016), (c) detecting loci under selection by allowing sliding‐window approaches along scaffolds (Hohenlohe, Phillips, & Cresko, 2010), and (d) finding the underlying genes associated with phenotype or adaptation (facilitated by mapping scaffolds to related species with well‐annotated genomes; e.g., Ekblom & Wolf, 2014; Kohn, Murphy, Ostrander, & Wayne, 2006; McKinney et al., 2016). In addition, it is possible with this information to estimate effective population size ( N e ; e.g., Li & Durbin, 2011) or effective number of breeders ( N b ) using LD‐based methods, as comparisons can be restricted to pairs of loci on different scaffolds, which should reduce or eliminate LD due to physical linkage.…”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
“…Amish et al, 2012;Hohenlohe et al, 2013). Of those, 10,267 SNPs could be mapped to anchored chromosomes in the recently published rainbow trout genome and therefore used to infer genomic location of the variant (Hand et al, 2015). This demonstrates the very high resolution capable from genotyping by NGS and the range of opportunities and applications available for conservation genomics.…”
Section: Introgressionmentioning
confidence: 98%
“…RADseq has proved to be a powerful approach for resolving the extent of admixture, with recently 16,788 putatively diagnostic SNPs identified that can distinguish cutthroat trout from rainbow trout (Hand et al, 2015), which advanced previous efforts along these lines (e.g. Amish et al, 2012;Hohenlohe et al, 2013).…”
Section: Introgressionmentioning
confidence: 99%